The Influence of Green Marketing, Content Marketing, and Environmental Awareness on the Purchase Decision of Honda Electric Cars in West Java - Medina Rachmadini; Zico Subekti; Rahmadi (Indonesian Journal of Business Analytics, 2026)
This community service activity aims to increase consumer understanding of the role of green marketing, content marketing, and environmental awareness in encouraging the purchase decision of Honda electric cars in West Java. The service was carried out through educational socialization accompanied by the distribution of questionnaires to 150 respondents as an evaluation of the impact of the activity. The implementation method uses a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis. The activity will be held in November 2025 in Cirebon. The results show that all three variables have a significant effect on purchasing decisions. These findings imply the importance of strengthening sustainable marketing strategies and environmental literacy to encourage environmentally friendly consumption behavior.